The Influence of Recruitment and Job Placement on Employee Performance at the Koperasi Konsumen Karyawan Keluarga Besar Petrokimia Gresik (K3PG) - Achmad Chabibi Isnani; Endang Iryanti (Indonesian Journal of Business Analytics, 2023)
Recruitment and placement play a crucial role in establishing a proficient Human Resources workforce inside an organization. This entails the process of strategically assigning employees or potential employees to work placements in order to enhance their efficiency in executing their workload and to foster the development of their skills. The objective is to ensure the smooth execution of tasks and to allocate individuals to positions and roles that align with their interests and abilities. The primary objective of this study, conducted inside the K3PG Cooperative, is to examine the extent to which recruitment and job placement practices impact employee performance. The K3PG Cooperative has received a response from a total of 53 individuals participating in the survey. The Structural Equation Modeling (SEM) method, in conjunction with the Partial Least Square technique and the SmartPLS 3.0 software, was used. To facilitate the implementation of data collection techniques, we conducted an extensive literature review and sent questionnaires to the participants. Based on the study results, it can be inferred that the process of recruitment has an impact on the performance of employees, while the placement of individuals in certain job roles has a discernible effect on the performance of workers employed by K3PG Cooperative.